Divergence of a Tandem Duplication of Manganese Superoxide Dismutase in Nosema bombycis. (7th August 2017) - Wang, Ying; Zhang, Ruizhi; Barandun, Jonas; Du, Huihui; Chen, Deming; Jia, Yuping; Song, Yue; Vossbrinck, Bettina; Li, Chong; Zhou, Zeyang; Vossbrinck, Charles R.; Xiang, Heng
Abstract: Manganese superoxide dismutase (MnSOD) is a key enzyme in the protection of cells from oxidative stress. A tandem duplication of the MnSOD gene ( NbMnSOD1 and NbMnSOD2 ) in the genome of Nosema bombycis, a parasite of the silkworm Bombyx mori, was previously identified. Here, we compare the protein structures of NbMnSOD1 and NbMnSOD2 and characterize these two proteins in terms of cellular localization, timing of transcription, protein structure, and enzyme activity. Despite a similarity in the primary sequence of NbMnSOD1 and NbMnSOD2, the latter shows a remarkable degree of amino acid sequence difference on the protein's surface and in the active site, where there is a substitution of a phenylalanine for a histidine in NbMnSOD2 . Immuno‐electron microscopy demonstrates that NbMnSOD1 is present in the cytosol of mature spores, whereas NbMnSOD2 is localized on the polar tube and the spore wall. Immunofluorescence confirms the localization of NbMnSOD2 on the polar tube of the germinated spore. Quantitative measurement of gene expression (qRT‐PCR) demonstrates production of both alleles during the first day of infection followed by a dramatic decrease during the second to fourth day of infection. From the fifth day onward, the two alleles show a complementary pattern of expression. The qRT‐PCR of the host manganese superoxide dismutase ( BmMnSOD ) shows a notable increase in transcription upon infection, leading to a three‐fold spike by the first day of infection, followed by a decrease in transcription. Measurement of overall MnSOD activity shows a similar peak at day 1 followed by a decrease to a constant rate of enzyme activity. The differences in cellular localization and pattern of gene expression of NbMnSOD2 compared to NbMnSOD1, as well as the differences in protein structure seen for NbMnSOD2 compared to other microsporidial MnSODs, strongly suggest a unique, recently evolved role for NbMnSOD2 .